Effects of ion irradiation on carbon nanotubes: a review. (1st January 2012) - Zhang, Yaoyao; Chen, Lei; Xu, Zhiwei; Li, Yinglin; Shan, Mingjing; Liu, Liangsen; Guo, Qiwei; Chen, Guangwei; Wang, Zhen; Wang, Chunhong
Ion irradiation with energetic particles can successfully be used for changing the properties of carbon nanotubes (CNTs) by functionalising, connecting, and creating defect structures in the CNTs. In this paper, we focus on the recent progress in our understanding of ion-irradiation-induced phenomena in CNTs. The production of defects (vacancies and interstitials) and the structural change of CNTs were reviewed. The ion induced modification of the properties was illustrated and the factors such as the substrate, the circumstance of the ion and the temperature which affect the defects and the properties of the ion-irradiated CNTs were also briefly investigated. By summarising the predecessors' research, we point out the issues which still lack complete investigating and further outline the most promising ways of using beams of energetic particles for CNT-related nano-engineering.